Pengaruh Lama Perendaman dan Konsentrasi KNO3 terhadap Viabilitas dan Vigor Benih Padi (Oryza sativa L.) - Grima Kharisma Yuliani; Ai Komariah; Kovertina Rakhmi Indriana (Paspalum: Jurnal Ilmiah Pertanian, 2023)
Rice is a staple food source for the majority of Indonesian, so the availability of ready-to-plant rice seeds is absolutely necessary. However, the continuity supply of quality rice seeds can be hampered by dormancy. The seed dormancy period can be broken by chemical methods, one of which is using a KNO3 solution. This study aimed to study the interaction of soaking time and KNO3 concentration on viability and vigor of rice seeds. This research were conducted at the BPSBTPH Laboratory Region 1 Cianjur. The research methodology used is a factorial randomized block design (RCBD) consisting of two factors and repeated 4 times. The first factor is the length of soaking time which consists of three levels, namely the duration of soaking 1 day, 2 days and 3 days and the second factor which consists of three levels, namely the concentration of KNO3 2%, 3% and 4% so as to produce 9 treatment combinations. The results showed that there was no interaction in all the observation parameters, both on viability and vigor of the seeds. However, independently, the 1 day soaking time factor (l1) gave the best effect on germination, germination height and vigor index, the 2-day soaking time (12) treatment gave the best effect on growth speed and root length, while the 2% concentration of (k1) gave the best effect on germination and growth speed on the first day of observation.